Brain Tumor Classification using MRI-Based Detection. - Obaid Dakheel, Ahmed; Singh, Yudhvir (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Brain tumor classification and segmentation is highly useful to provide proper care for the patients. Identification of early disease detection can safeguard the life of the patients. The research paper has reviewed the literature with 66 previously published research papers on Image comparison for brain tumor disease using artificial intelligence based machine learning algorithms[1]. The research paper has explored the insights of image processing in detection of brain tumor images obtained from various diagnosis centers in UK and India. The fundamental working principles of deep learning concepts can generate efficient diagnosis of brain tumor disease[2]. The report also presented the experimental results conducted using MATLAB Simulink with the implementation of Convolutional Neural Networks. The results demonstrated that convolutional neural networks can perform the diagnosis with high accuracy within shortest period of time.